Neutrophil extracellular traps in diseases of the female reproductive organs - Morawiec, Maria-Laura; Kubina, Robert; Stępień, Sebastian; Smycz-Kubańska, Marta; Królewska-Daszczyńska, Patrycja; Ratajczak-Wrona, Wioletta; Mielczarek-Palacz, Aleksandra (Frontiers in Immunology, 2025)
Neutrophil extracellular traps (NETs) are physiologically released in response to pathogens, serving as a defense mechanism. However, excessive NET production has been implicated in various pathological conditions, including diseases of the female reproductive system. Recent studies highlight the significant role of neutrophils and NETs in cancer pathogenesis. Overproduction of NETs creates sites for tumor cell adhesion, promoting tumor cell proliferation, immune escape, and tumor progression. NET formation is associated with many diseases, including cancers of the female reproductive organs. Detection of NETs can be used as a prognostic tool for patients with diseases characterized by higher rates of NETs formation, such as cancer. In order to use NETs in diagnosis, it is possible to determine them directly or to determine NET components: extracellular DNA, citrullinated histones, NE or MPO. This review explores the role of neutrophils and NETs in the pathogenesis, diagnosis and treatment of breast, ovarian, cervical and endometrial cancer, premature lapse of ovarian function, cervicitis, endometriosis, pregnancy and pregnancy-related diseases.